1185The association between neighbourhood built environment and health-related fitness: A systematic review. (2nd September 2021) - Frehlich, Levi; Christie, Chelsea; Ronksley, Paul; Turin, Tanvir C; Doyle-Baker, Patricia; McCormack, Gavin
Abstract: Background: Few studies have investigated potential links between the built environment and health-related fitness, even though there is some evidence linking neighbourhood built environments to physical activity behaviors and chronic health conditions. Methods: Following PRISMA guidelines eight databases were searched from inception to August 2020 using a combination of built environment and health-related fitness terms. Inclusion criteria was limited to quantitative studies that sampled of adults aged 18 years or older with no physical disabilities or health issues that may impact health-related fitness. Results: Of the 26, 219 citations identified within our comprehensive search, 25 studies met eligibility and underwent data extraction and quality assessment. Objectively measured built environment characteristics (e.g., improved sidewalks, higher street connectivity, older neighbourhoods, higher residential density, and higher land use mix) were associated with increased flexibility, cardiorespiratory fitness, grip strength, and body composition. Moreover, perceptions of neighbourhood features such as higher neighbourhood walkability, greater park access and quality, and lower neighbourhood crime, were associated with increased perceived cardiorespiratory fitness, muscular strength, flexibility, and overall fitness. However, many of these findings were from cross-sectional studies where adjustment for key confounders varied. Results also varied by sex in the small number of studies that provided sex-specific stratifications. Conclusions: This project may help elucidate the pathway between the built environment and health-related fitness. Key messages: Neighbourhood built environment features are associated with aspects of health-related fitness.